Improving Operational Management Efficiency in the Food and Beverage Industry: A Systematic Literature Review - Enrica Ryan Geminarqi; Purnomo, Hery (HM Publisher, 2023)
Improving operational management efficiency is not just an option but a necessity to maintain competitiveness in a rapidly changing market. By optimizing production processes, inventory management, customer service, and utilization of technology, companies can reduce operational costs, increase speed and accuracy in service, and improve the quality of products served to customers. This study seeks to explore several strategies and steps that can be taken by companies in the food and beverage industry to improve the efficiency of their operational management. The literature search process was carried out on various databases (PubMed, Web of Sciences, and Google Scholar) regarding the analysis of improving operational management efficiency in the food and beverage industry. This study follows the preferred reporting items for systematic reviews and meta-analysis (PRISMA) recommendations. Improving operational management efficiency in the food and beverage industry is a continuous process. By implementing process automation, intelligent data analysis, employee training, efficient inventory management, collaboration with suppliers, and a focus on quality and customer service, companies can achieve these goals. This effort will help the company to remain competitive and sustainable amid increasingly fierce and dynamic competition in the food and beverage industry.